Florid cystitis glandularis (intestinal type) with mucus extravasation: Two case reports and literature review - Zhang, Tao; Yin, Si-Fan; Feng, Wen-Bo; Ke, Chang-Xing (Frontiers in Surgery, 2023)
Background Cystitis glandularis is a common bladder epithelial lesion characterized by hyperplasia and metaplasia of the bladder mucosa epithelium. The pathogenesis of cystitis glandularis of the intestinal type is unknown and less common. When cystitis glandularis (intestinal type) is extremely severely differentiated, it is called florid cystitis glandularis (the occurrence is extremely rare). Case summary Both patients were middle-aged men. In patient 1, the lesion was also seen in the posterior wall and was diagnosed more than 1 year ago as cystitis glandularis with urethral stricture. Patient 2 was examined for symptoms such as hematuria and was found to have an occupied bladder; both were treated surgically, and the postoperative pathology was diagnosed as florid cystitis glandularis (intestinal type), with mucus extravasation. Conclusion The pathogenesis of cystitis glandularis (intestinal type) is unknown and less common. When cystitis glandularis of the intestinal type is extremely severely differentiated, we call it florid cystitis glandularis. It is more common in the bladder neck and trigone. The clinical manifestations are mainly symptoms of bladder irritation, or hematuria as the main complaint, which rarely leads to hydronephrosis. Imaging is nonspecific and the diagnosis depends on pathology. Surgical excision of the lesion is possible. Due to the malignant potential of cystitis glandularis of intestinal type, postoperative follow-up is required.